Power system impacts of electric vehicles in Germany: Charging with coal or renewables? - Wolf-Peter Schill; Clemens Gerbaulet (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We analyze future scenarios of integrating electric vehicles (EV) into the German power system, drawing on different assumptions on the charging mode. We use a numerical dispatch model with a unit-commitment formulation which minimizes dispatch costs over a full year. While the overall energy demand of the EV fleets is rather low in all scenarios, the impact on the system's load duration curve differs strongly between charging modes. In a fully userdriven mode, charging largely occurs during daytime and in the evening, when power demand is already high. User-driven charging may thus have to be restricted in the future because of generation adequacy concerns. In contrast, cost-driven charging is carried out during night-time and at times of high PV availability. Using a novel model formulation that allows for intermediate charging modes, we show that even a slight relaxation of fully userdriven charging results in much smoother load profiles as well as lower charging costs. Different charging patterns go along with respective changes in power plant dispatch. By 2030, cost-driven EV charging strongly increases the utilization of lignite and hard coal plants, whereas additional power in the user-driven mode is predominantly generated from natural gas and hard coal. Specific CO2 emissions of EV are substantially larger than those of the overall power system, and highest under cost-driven charging. Only in additional model runs, in which we link the introduction of EVs to a respective deployment of additional renewable generation capacity, electric vehicles become largely CO2-neutral.
Keywords: Q42; R41; Q54; 330; electric vehicles; power system; dispatch model; renewable energy